Surgical glue in laparoscopic sleeve gastrectomy: An initial experience and cost‐effectiveness analysis. Issue 3 (21st March 2017) - Mercier, Gregoire; Loureiro, Marcelo; Georgescu, Vera; Skalli, El Mehdi; Nedelcu, Marius; Ramadan, Mohamed; Fabre, Jean Michel; Lefebvre, Patrick; Nocca, David
Abstract: Rationale, aims, and objectives: Laparoscopic sleeve gastrectomy (LSG) is one of the most common bariatric procedures. Gastric leaks and bleeding are the most frequent complications, associated with a high clinical and economic burden. The best method of staple line reinforcement in LSG is debated. Surgical glue is one of the options available. The aim of this study was to assess the safety, efficiency, and relative cost‐effectiveness of surgical glue used to perform LSG in morbid obese adults as compared with standard stapling. Methods: A prospective, observational, and comparative before‐after study was conducted. All consecutive patients undergoing LSG at Montpellier University Hospital in 2011 and 2012 were included and treated according to 2 groups: standard stapling (n = 99, group 1) and surgical glue reinforcement (n = 94, group 2). Clinical and economic outcomes were measured after 6 months. Results: The duration of intervention was significantly shorter in group 2 (68 vs 82 minutes, P  = .001). There was no significant difference regarding complications, but leaks in group 1 were more severe. Group 2 was also associated with a reduced initial length of stay (4.8 vs 5.2 days, P  = .01). Six‐month readmissions and total length of stay were also shorter in group 2 (5.5 vs 6.1 days, P  = .003). Surgical glue use was associated with a significant reduction in the initial inpatient cost (€5488 vs €6152, P  = .005) and in the 6‐month total inpatient cost, including readmissions (€6006 vs €6754, P  = .005). The incremental cost of glue to avoid a severe complication was −€5446.33 (95 confidence interval, −8202.01 to −2690.66). Conclusions: Surgical glue might be a safe and cost‐effective intervention in laparoscopic sleeve gastrectomy.